Penerapan Pembelajaran Detach Strategy Activation pada Mata Kuliah Bahasa Arab Semester I (Satu) di STIT Raden Wijaya Mojokerto - Afif, Muthoharun (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2016)
Attempts to teach Arabic in Indonesia has been around a long time, perhaps since Islam came to Indonesia. At first the Arabic language is taught according to the needs of Muslims as a language of worship, even now many Indonesian people who speak Arabic in its function as a language of worship, then the Arabic language are taught to understand the religious sources as al-Qur'an, Hadith, Tafseer , etc. Efforts to implement the lecturers Detached Strategy Activation is one of the strategies to improve student learning outcomes Arabic and enhance the activity of students in the classroom. Arabic saturated, boring and scary expected to be avoided. Lecturers can discuss with fellow colleagues in developing or designing the learning problems of Arabic in an interesting context issues, student environmental conditions, as well as facilities and media facilities available. Cognitive learning in the form of Detached Strategy Activation form of stimulation of cognitive considered capable of providing a learning experience meant as a reference for lecturers in implementing learning activities that can be a result of observations, data, facts, concepts, theories, laws, opinions, information print and electronic media as well as the results of research , Expected future faculty can continue to design / plan, monitor, evaluate, and reflect as well as continue to improve the shortcomings, difficulties and can overcome the problem so that students understand the mathematical concept is flexible, accurate, efficient, and precise and have respect for the usefulness of mathematics in life ie have a curious or critical, attention and interest in studying Arabic, as well as a tenacious attitude and believe themselves in problem solving learning Arabic.